Significance of the International Study Pirls in Education in Uzbekistan (Eurasian Research Bulletin, 2023)
International educational research plays an important role in assessing the effectiveness of different countries' education systems and developing strategies to improve them. One such study is PIRLS - the Primary International Reading Literacy Study. This study assesses the reading literacy levels of primary school students in different countries and identifies factors that influence their success in this area. This article examines the significance of the international PIRLS study in the context of education in Uzbekistan